2003
DOI: 10.1037/0012-1649.39.5.877
|View full text |Cite
|
Sign up to set email alerts
|

Development of attention and distractibility in the first 4 years of life.

Abstract: This observational study describes the early development of attention and discractibility. Under several conditions of distraction, 172 children at 10, 26, and 42 months of age played with toys. Attention to the toys was coded as casual, settled, or focused. All 3 levels of attention changed with age, withcasual attention decreasing and focused attention increasing. The 10-month-olds were more distractible than the other children, even during focused attention. The infants were most distracted by the auditory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
174
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(185 citation statements)
references
References 50 publications
11
174
0
Order By: Relevance
“…Both Turnure and Higgins and Turnure also found that the same distracter actually enhanced focal attention among slightly older children, resulting in enhanced performance on the pattern-recognition task. Ruff and Capozzoli (2003) reported a similar "mobilization of attention" in the presence of environmental distracters in children as young as 3.5 years of age. Turnure hypothesized that for some children under some conditions, the presentation of an environmental distraction might actually funnel children's attention to a target task, resulting in improved task performance.…”
mentioning
confidence: 62%
“…Both Turnure and Higgins and Turnure also found that the same distracter actually enhanced focal attention among slightly older children, resulting in enhanced performance on the pattern-recognition task. Ruff and Capozzoli (2003) reported a similar "mobilization of attention" in the presence of environmental distracters in children as young as 3.5 years of age. Turnure hypothesized that for some children under some conditions, the presentation of an environmental distraction might actually funnel children's attention to a target task, resulting in improved task performance.…”
mentioning
confidence: 62%
“…EA is consciously effortful, focused, and less prone to distractions (Posner & Rothbart, 2007), and varies as a function of social interactions, emotional ties, and object interest. Ruff and Capozzoli's (2003) study placed EA within the context of alerting (casual attention) and orienting (settled attention: pausing in casual attention to look steadily at a toy). Focused attention (EA) was defined by concentration with intent facial expression, close visual inspection of toy, and minimal extraneous body movement.…”
Section: Developmental Regulatory Processesmentioning
confidence: 99%
“…14 The lack of attention errors score seen was inversely proportional to age, that is, higher values attained at younger ages indicate that older children perform better and make fewer mistakes than smaller children, in agreement with the literature. 8,12,[15][16][17] Younger children have a more limited attention span, and as they grow, there are changes in their inner processing mechanisms that increase this capacity. 18 Younger individuals seem to have a more impulsive behavior than their older counterparts 11 , in accordance with the present investigation.…”
Section: Discussionmentioning
confidence: 99%